Vitro Antioxidant Potency of Tinospora cordifolia (gulancha) in Sequential Extracts - KR, Anilakumar (International Journal of Pharmaceutical & Biological Archive, 2011)
Background: Tinospora a medicinal herb used in the Indian system of medicine due to their health benefits. The stem of the plant was studied for its antioxidant and phytochemical constituents. Sequential extraction of the powder was done with different solvents with increasing polarity. The antioxidant activity of polar to non-polar solvents extracts of the herb was evaluated by various antioxidant assays. The phytochemical constituent such as total phenols, flavonoids, tannins, and proximate compositional analysis was carried out. Results: Methanolic, ethanolic and water extracts showed significant antioxidant potential compared to other solvents and also possess metal chelation and reducing power activity. In the DPPH radical scavenging activity, methanolic extract (98.13%) showed high antioxidant potency, ethanolic extract (90.34%) was a potent scavenger of superoxide radical. At the same time, both methanolic (97.08%) and ethanolic extracts (95.21%) inhibited hydroxyl radical along with other extracts. The metal chelation in methanolic (60.62%), ethanolic (57.62%), aqueous extracts (40.89%) and reducing of ferrous ions was significant found increasing in methanolic, ethanolic and aqueous extracts. Conclusion: The stem of Tinospora cordifolia has potential application in food systems as an antioxidant and probably in biological systems as a nutraceutical.